Metal-resistant microorganisms of tap water: theoretical justification and biotechnological application - Havryliuk, O.A.; Bida, I.O.; Hovorukha, V.M.; Danko, Y.P.; Gladka, G.V.; Sachko, A.V.; Yastremska, L.S.; Tashyrev, O.B.; Muchnyk, Ph.V. (Problems of Environmental Biotechnology, 2021)
Water is one of the most essential resources for all living things. The issue of drinking water quality is acute both in Ukraine and in other countries due to the development of industry, as well as the constant growth of the world’s population. After purification and disinfection of water at water treatment plants and then in the water supply system, water quality is not controlled. An important indicator that determines the quality of water is its microbial composition. Microorganisms get into water mains from water intake sites and live and multiply in outdated and modern systems of drinking water distribution. In the sample of tap water, which was taken from the water supply system of Kyiv, we determined a significant content of microorganisms – 2.45×103 CFU/mL. The number of chemoorganotrophic microorganisms in the filler, which was removed from the filter cartridge for water purification, was also high – 1.6×105 CFU/g. In addition, the filler for water filtration contained thousands and tens of thousands of metal-resistant microorganisms. Thus, the maximum permissible concentration (MPC) of Cu(II) (ionic form) for the microbiome of the filter was 125 ppm, as well as Cr(VI) – 350 ppm. The concentration of living microorganisms in the medium was 2.91×105 CFU/g of filter at the presence of MPC of Cu(II). The number of microorganisms was 9.7×102 CFU/g at the presence of Cr(VI) (in form of CrO42-) in the nutrient medium. The resistance of the microbiome of the water filter to Cu(II) chelated by citrate was investigated, becouse heavy oxidizing metal compounds are able to precipitate in biological media. It was found that the resistance of microorganisms to Cu(II) citrate was 28 times higher than to the ionic unchelated form and amounted to 3500 ppm. The isolated microbiome is polyresistant and has a high adaptive potential to action of toxic metal compounds.